LITERATURE REVIEW : THE EFFECT OF PROBLEM BASED LEARNING (PBL) LEARNING MODEL ON STUDENTS' CRITICAL THINKING - Hakim, Lukmanul; Fitriati, Desy; Fitriani, Desy; Hasanah, Ulfatun; Surur, Miftahus (STKIP PGRI Situbondo, 2025)
Education is critical because, without education, it is difficult for society to develop and will be left behind. Education is one of the efforts to improve the quality of human energy sources, encompassing both physical, mental, and spiritual aspects. The problem-based learning (PBL) learning model is one of the learning models that can help students develop their critical thinking skills to solve problems. This study aims to determine the influence of the Problem-Based Learning (PBL) model on students' critical thinking skills. The method used in this study is a literature review. A total of 15 relevant articles were selected and analyzed to determine the influence of the Problem-Based Learning (PBL) model on students' critical thinking skills. The results of this literature review indicate that the Problem-Based Learning (PBL) model has a significant impact on improving students' critical thinking skills. Through Problem-Based Learning (PBL), students engage in a real-world problem-solving process, encouraging them to think analytically, critically, and creatively.